Validity and Reliability of Executive Function Measures in Children with Heavy Prenatal Alcohol Exposure: Correspondence Between Multiple Raters and Laboratory Measures - Bernes, Gemma A. (Alcohol Clin Exp Res, 2021)
BACKGROUND: Rating scales are designed to complement traditional performance-based measures, and both can provide useful information about the functioning of youth with histories of prenatal alcohol exposure. Few studies, however, have compared ratings from multiple informants or the relationship between these subjective rating scale scores and the objective results from laboratory performance-based scales. METHODS: The current study addressed both of these questions in three study groups: children with histories of prenatal alcohol exposure (AE; n = 47), attention-deficit/hyperactivity disorder (ADHD; n = 41), and typically developing controls (CON; n = 73). All subjects completed a standardized neuropsychological test battery, including laboratory measures of executive functioning and a self-report measure of executive function behaviors. Parents and teachers completed corresponding rating scales of executive function behaviors for each subject. This study assessed the relationship between these behavior rating scales and corresponding neuropsychological tests, and inter-rater agreement among the multiple informants. RESULTS: Weak correlations were found between the rating scales and laboratory measures, indicating poor convergent validity for the behavior rating scale. Inter-rater reliability was found but differed by group. Agreement was found between parent and teacher ratings for children with prenatal alcohol exposure, whereas teacher-child agreement was found for those with ADHD. CONCLUSION: Findings from this study indicate that behavior ratings can be used to supplement laboratory measures but may not be measuring cognitive abilities regardless of whether a clinical diagnosis is present. A multi-method approach should be used when measuring skills in this domain. This was one of the first studies to examine cross-informant agreement in a sample of children with prenatal alcohol exposure. Further research is necessary to understand why inter-rater agreement differed for children with prenatal alcohol exposure and those with ADHD.